Graduate training during the COVID‐19 pandemic: North American genetic counseling students' challenges, intolerance of uncertainty, and psychological well‐being. Issue 5 (19th October 2021) - Kahn, Eva; Sheldon, Jane P.; Carmichael, Alicia; Yashar, Beverly M.
Abstract: The COVID‐19 pandemic has upended genetic counseling (GC) graduate students' lives, as they have been forced to transition, manage, and acclimate to life during a pandemic. The current study is a first step in understanding their lived experiences during this historic, global event. We investigated academic and personal challenges, intolerance of uncertainty, and psychological well‐being of GC students ( n = 248) who trained during the pandemic (GC‐COV cohort) and those who did not (GC‐NoCOV cohort). Participants completed an online survey (July–September 2020) that used validated measures of Intolerance of Uncertainty and Psychological Well‐Being. To assess the academic and personal challenges students experienced during GC graduate training, we developed a 43‐item measure. Principal axis factoring of the items revealed categories of challenges related to the following: Academic & Professional Development, Self‐Regulation & Resilience, Institutional & Program Leadership, and Financial Stability. There was no cohort difference in Psychological Well‐Being. Linear mixed‐effects modeling showed significant cohort differences in challenges. Multiple linear regression analyses revealed that the GC‐COV cohort's Psychological Well‐Being was statistically significantly predicted by Institutional & Program Leadership challenges ( p = .029), Self‐Regulation & Resilience challenges ( p = .013), and Intolerance of Uncertainty ( p = .010). For the GC‐NoCOV cohort, the statistically significant predictor of Psychological Well‐Being was Self‐Regulation & Resilience challenges ( p = .029). Our findings demonstrate that GC students training during the COVID‐19 pandemic have experienced various personal, academic, and psychological disruptions and highlight a need to develop resources and implement interventions supporting students' academic development and psychological well‐being.